Satisfaction level using e-learning among undergraduate nursing students at school of Health Sciences, USM - A/L Suppramaniam, Pugelalaggen (2020)
The satisfaction of students is one of the most important factors in determining the performance of e-learning program implementation. This study aimed to assess the satisfaction level using e-learning among nursing students at the School of Health Sciences, USM, Kelantan. A cross-sectional survey was conducted using a questionnaire adapted from Bolliger’s (2004) OCSS. A total of 110 undergraduate nursing students were recruited via stratified random sampling. In this study, 90.0% of the undergraduate nursing students were satisfied using e-learning. Results also revealed that the highest mean score corresponds to the website and the lowest mean score corresponds to interactivity. One-way ANOVA test was used to determine the difference in satisfaction level towards e-learning between the year of study among undergraduate nursing students. There was a significant difference between undergraduate nursing students’ satisfaction score using e-learning and the year of study (p= 0.002). The satisfaction score of the students using e-learning decreases as the year of study increases. Moreover, the Kruskal-Wallis test was conducted to evaluate the difference between satisfaction level towards e-learning and the CGPA score nursing undergraduate students. There was no significant difference between satisfaction level towards e-learning and the CGPA score nursing undergraduate students (p> 0.05). In conclusion, the study found that undergraduate nursing students were highly satisfied using e-learning at School Of Health Sciences.